Clinical significance of detection of multiple acute brain infarcts on diffusion weighted magnetic resonance imaging. Issue 4 (16th March 2005) - Caso, V; Budak, K; Georgiadis, D; Schuknecht, B; Baumgartner, R W
Abstract : Background: Detection of multiple acute brain infarcts (MABI) by diffusion weighted magnetic resonance imaging (DWI) may provide information about stroke mechanism in (1) acute lacunar stroke, where evidence of MABI suggests a cause other than small artery disease (SAD), such as embolism or vasculitis (type 1 MABI); or (2) acute non-lacunar stroke, where MABI in the territory of at least two of the aortic branches supplying the brain indicates the presence of aortic or cardiac embolism rather than artery to artery embolism (type 2 MABI). Objective: To evaluate the prevalence of MABI and their impact on aetiological classification and prevention of stroke in patients with acute ischaemic stroke examined with DWI. Methods: 182 consecutive patients defined by DWI were evaluated. Stroke aetiology was classified according to the TOAST criteria, though "lacunar stroke" included patients with possible aetiologies other than SAD. Results: Type 1 MABI were detected in 21/72 patients (29%) with lacunar stroke, and type 2 MABI in 8/110 (7%) with non-lacunar stroke. A possible stroke mechanism different from SAD was found in nine type 1 MABI cases (43%): cardiac embolism (4); other determined aetiology (3); aortic embolism (2). Cardiac (2) or aortic (1) sources of embolism were detected in eight type 2 MABI cases. MABI patients with cardiac or aortic sources of embolism were treated with warfarin, the remainder with aspirin. Conclusions: Detection of type 1 MABI in patients with lacunar stroke improved diagnostic confidence and the choice of antithrombotic treatment. Further study is needed on stroke prevention in MABI cases caused by SAD alone.